The Wilms tumor gene (WT1) (+/−KTS) isoforms regulate steroidogenesis by modulating the PI3K/AKT and ERK1/2 pathways in bovine granulosa cells. Issue 5 (14th January 2019) - Meng, Kai; Wang, Xiaomei; He, Yuanyuan; Yang, Jiashu; Wang, Hengqin; Zhang, Yong; Quan, Fusheng
Abstract: The Wilms tumor (WT) gene WT1 encodes the splicing variants WT1(+KTS) and WT1(−KTS). Recent data suggest that WT1 plays an important role in the development of mice follicles. However, the mechanism through which WT1 influences ovarian steroidogenesis remains unknown. This study identified WT1 and evaluated the impact of splicing variants WT1(+KTS) and WT1(−KTS) on steroidogenesis using adult bovine granulosa cells (GCs). Using RT-qPCR and western blotting, we found that the ratio between WT1(+KTS) and WT1(−KTS) was stabilized. WT1 expression, however, decreased gradually in bovine GCs in response to follicle enlargement or atresia. The downregulation of WT1 increased the secretion of basal and follicle-stimulating-hormone-induced progesterone (P4), but decreased the secretion of basal-induced estradiol (E2). This was associated with an increase in the expression of 3β-HSD, and a decrease in the expression of CYP19A1 . In addition, WT1(−KTS) overexpression suppresses the secretion of E2 and P4 compared with WT1(+KTS) overexpression. This was associated with a decrease in the expression of CYP19A1, CYP11A1, and 3β-HSD in cultured bovine GCs. Of note, the downregulation of WT1 suppresses the phosphorylation levels of AKT and p-ERK1/2. However, WT1(−KTS) overexpression promotes the phosphorylation levels of AKT and suppresses p-ERK1/2 levels. LY294002 (AKT inhibitor) increases MKP3 mRNA expression levels but decreases the level of p-AKT and p-ERK1/2. Collectively, WT1 significantly suppresses the mRNA expression of CYP11A1 and 3β-HSD and the secretion of P4 in bovine GCs. Moreover, it regulates CYP19A1 mRNA expression and E2 secretion with complex networks, at least in part, by modulating AKT and ERK1/2 signaling. The effect of WT1(−KTS) was more pronounced than that exerted by WT1(+KTS). Abstract : This study showed the effect of WT1(+/−KTS) on the steroidogenesis of GCs, and elucidated the role of the PI3K/AKT and ERK1/2 pathways in WT1-regulated steroidogenesis.